Distinct Role of Lycium barbarum L. Polysaccharides in Oxidative Stress-Related Ocular Diseases - Yali Niu; Guoheng Zhang; Xiaojia Sun; Shikun He; Guorui Dou (MDPI AG, 2023)
Oxidative stress is an imbalance between the increased production of reactive species and reduced antioxidant activity, which can cause a variety of disturbances including ocular diseases. Lycium barbarum polysaccharides (LBPs) are complex polysaccharides isolated from the fruit of L. barbarum, showing distinct roles in antioxidants. Moreover, it is relatively safe and non-toxic. In recent years, the antioxidant activities of LBPs have attracted remarkable attention. In order to illustrate its significance and underlying therapeutic value for vision, we comprehensively review the recent progress on the antioxidant mechanisms of LBP and its potential applications in ocular diseases, including diabetic retinopathy, hypertensive neuroretinopathy, age-related macular degeneration, retinitis pigmentosa, retinal ischemia/reperfusion injury, glaucoma, dry eye syndrome, and diabetic cataract.